The Effect of High Fructose Corn Syrup on SCC-9 Cells Regulated by G0/G1 Cell Cycle Arrest via Apoptosis Induction - Kavitha, Kalimuthu; Sindhu, Ganapathy; Porkodi, Marimuthu; Asha, Kumarasamypillai Radha Thayammal; Veeravarmal, Veeran; Vijayalakshmi, Annamalai (Asian Journal of Biological and Life Sciences)
Aim: The current study’s objective was to assess high fructose corn syrup (HFCS) affected oral squamous cell carcinoma (OSCC) SCC-9 cells through apoptosis, DNA fragmentation, and the cell cycle. Materials and Methods: The MTT experiment showed that treatment of SCC-9 cells with HFCS causes internucleosomal DNA breakage and loss of cell viability in a concentration-dependent manner, with an IC50 of 679.2 µM. PI and Annexin-FITC labelling were utilized to evaluate the apoptotic nuclear characteristics and migration by fluorescence microscope and flow cytometry during HFCS therapy for apoptosis and cell cycle arrest. Results: Key findings are HFCS decreased the cell viability (IC50 values of 679.2 µm), reduced migration, enhanced DNA fragmentation and decreased colony formation in SCC-9 cells and Caspase 3 and 9 gene expressions. DNA fragmentation assay revealed HFCS might cause oxidative DNA damage in SCC-9 cells significantly (p < 0.05). Similarly, we observed apoptotic stage changes in HFCS-treated cells. Furthermore, HFCS-treated SCC9 cells accumulated in the G0/G1 phase compared to the standard drug Colchicine. All things considered, the results suggest that HFCS affects the SCC-9 cell line by causing DNA damage, cell cycle arrest at the G0/G1 phase, and production of caspase 3 and caspase 9. Conclusion: Contrary to earlier literature, our study concluded that higher concentrations of HFCS (500 and 1000µM) reduce cell viability, cell migration and enhance apoptosis in oral cancer cells SCC-9. So that these findings may be generalised to human intake equivalent, more research is needed to confirm its effect on predisposition to mouth cancer.
Keywords: HFCS; Oral cancer; MTT; Cell cycle arrest; Apoptosis; Cell migration